The Lexical Comparison between Tanjung Bonai Aur Sub Dialect in Sijunjung and Standard Minangkabaunese - Zara Afnar Wansyah; Jufrizal Jufrizal (Universitas Negeri Padang, 2023)
A lexical comparison is a comparison of dialects that may different lexicon, grammar and pronunciation. The aims of this study are (1) to find out the lexical similarities of between Tanjung Bonai Aur sub dialect and Standard Minangkabaunese (2) to find out the lexical differences between Tanjung Bonai Aur sub dialect and Standard Minangkabaunese. Type of this research was the descriptive techniques,it is likely to compare between Tanjung Bonai Aur sub dialect and Standard Minangkabau language to see how closely these dialects are related. In this research, elicitation techniques were used by the researcher to get information from informants. Then, the researcher used notebook and recorder as instruments. From the result of finding, it is clears that Tanjung Bonai Aur sub dialect has a very closely related with standard Minangkabau language, because one of the Minangkabau dialects is Tanjung Bonai Aur. The differences occur in vocabulary and pronunciation. There are five differences in Tanjung Bonai Aur sub dialect (1) phoneme /a/ becomes /o/ in first syllable, (2) phoneme /r/ becomes /w/ in the middle syllable, (3) phoneme /a/ changes into /əu/ at the end syllable, (4) phoneme /r/ becomes /ɰ/ in the middle syllable, (5) and full lexicon differences. The difference is caused by geographical factor.